Narratives of Developing Islamic Education Modules Based on Local Wisdom and Prophetic Values - Hubban Jamma; Eva Ardinal; Abdul Salam; Aiman Fariq; Sara Hussain (Yayasan Adra Karima Hubbi, 2026)
Background. This research is motivated by the need to develop Islamic Religious Education (PAI) teaching materials that are not only normative-doctrinal in nature, but also contextual to the socio-cultural realities of students. To date, PAI modules tend to be less accommodating of local wisdom and prophetic values that encompass the dimensions of humanization, liberation, and transcendence, so that learning has not fully formed a holistic character. Purpose. Therefore, this study aims to develop an PAI module based on local wisdom and prophetic values that is valid, practical, and effective in improving the quality of learning. Method. The research method used is research and development (R&D) with a development model that includes the stages of needs analysis, product design, expert validation, limited trials, and product revision. The research instruments are in the form of validation sheets, student response questionnaires, and learning outcome tests. Results. The results show that the developed module has a high level of validity based on expert assessments, and is considered practical and easy to use in the learning process. Furthermore, the implementation of this module has proven effective in enhancing students' understanding of Islamic Religious Education (PAI) material while simultaneously instilling local wisdom and prophetic values in everyday life. The research discussion confirms that the integration of local wisdom and prophetic values in the PAI module can create more contextual, relevant, and meaningful learning. Conclusion. The development of a PAI module based on local wisdom and prophetic values is a strategic innovation in improving the quality of Islamic religious education that is adaptive to local culture while also oriented towards the comprehensive character development of students.